2004
DOI: 10.1021/es035323k
|View full text |Cite
|
Sign up to set email alerts
|

Global Pollution Monitoring of Polybrominated Diphenyl Ethers Using Skipjack Tuna as a Bioindicator

Abstract: To elucidate the global distribution of polybrominated diphenyl ethers (PBDEs), these chemicals were determined in the muscle of skipjack tuna (Katsuwonus pelamis) collected from offshore waters of various regions in the world (Japan, Taiwan, Philippines, Indonesia, Seychelles, and Brazil, and the Japan Sea, East China Sea, South China Sea, Indian Ocean, and North Pacific Ocean). PBDEs were detected in almost all the skipjack tuna collected from the locations surveyed (from < 0.1 to 53 ng/g of lipid), indicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
76
3
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(91 citation statements)
references
References 15 publications
10
76
3
2
Order By: Relevance
“…The declining ΣPBDE concentrations in fur seals from Northern Japan during the 1990s suggests that eastern Asia was not a strong source region for Br4-Br6-PBDEs in the northern Bering Sea and Chukchi area. PBDEs (Br4-Br6) in skipjack tuna (Katsuwonus pelamis) from the central North Pacific were also much lower than in samples from the Japan Sea and the East China Sea (38).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…The declining ΣPBDE concentrations in fur seals from Northern Japan during the 1990s suggests that eastern Asia was not a strong source region for Br4-Br6-PBDEs in the northern Bering Sea and Chukchi area. PBDEs (Br4-Br6) in skipjack tuna (Katsuwonus pelamis) from the central North Pacific were also much lower than in samples from the Japan Sea and the East China Sea (38).…”
Section: Resultsmentioning
confidence: 87%
“…The detection of BDE183 and BDE209 in the plasma of female Svalbard bears (24) also suggests exposure of bears to BDE183 and BDE209 in the food web and this could be underestimated as a consequence of metabolic debromination. Ueno et al (38) found higher ratios of BDE 47/99 in skipjack tuna with increasing latitude in the western North Pacific Ocean which they attributed to greater long-range transport of BDE47. Thus discrimination among isomers during long-range transport, as well as during bioaccumulation and metabolism, is influencing the congener pattern observed in polar bears and, as a result, source signatures could be lost.…”
Section: Resultsmentioning
confidence: 97%
“…PBDEs are now as ubiquitous as PCBs in the aquatic environment, and their levels are rising due to a lack of regulation (35,36). It is now believed that PBDEs have spread throughout the world's oceans (35,37), and as a consequence have been found in many aquatic organisms, including fish, where they have bioaccumulated to biologically relevant levels (33). The aquatic environment of the fish we investigated is one of the most contaminated regions worldwide, and studies have shown PBDE levels in breast milk from women living in the San Francisco Bay area up to 100 times greater than those in other regions of the world (8).…”
Section: Discussionmentioning
confidence: 99%
“…The electronic waste (e-waste) recycling especially uncontrolled dismantling aggravated the process (Julander et al 2005). So PBDEs become ubiquitous in the environment (Ueno et al 2004). Furthermore, most toxicological studies have shown that serious health consequences, such as thyroidogenic, estrogenic, and hepatic effects as well as neurodevelopmental disorders, could result from prolonged exposure to PBDEs (Darnerud et al 2001).…”
mentioning
confidence: 99%